LANGUAGE POLICY IN EUROPE - BABYLON OF THE XXI CENTURY - K. Kh. Rekosh (Vestnik MGIMO-Universiteta)
In recent decades, much has been written about the dialogue of cultures and differences between them manifested by languages, which are the objects of interdisciplinary research. However, the active role of multiplicity of languages and their interaction in particular with the relevant areas of knowledge do not always attract the proper attention. Along with many languages, Europe seeks to move away from monolingualism in favor of multilingualism, recognizing that it is promising, so political actors support it. The principles of multilingualism have been adopted in the international (European) and national levels and formalized in terms of plurilingualism and multilingualism. The plurilingualism is the use of multiple languages by one and the same person. It is an integral part of cultural diversity and respect, a necessary condition for human development as a professional and as a person. The multilingualism is denoted by a policy of equality of languages in the community. The European Union is a multilinguistic organization. Language policy of the European Union has been defined since the establishment of the communities, it was different from the language policies of other international organizations and was based on the principle of cultural and linguistic diversity (although the term multilingualism was not used) with the aim of ensuring access to information and justice for all EU citizens in all official EU languages. Held in Europe language policy led to the institutionalization of the concept of multilingualism, particularly by the European union, which could serve to the development of linguistic law. The EU language policy is linked with the objectives of the integration law which makes it different from the plurilingualism. It acts as an instrument for intercultural dialogue and social cohesion, as a guarantee of prosperity and employment opportunities. At the same time it generates a lot of linguo-legal problems concerning different statuses of languages; EU official languages, working, state, regional, national languages, as well as minorities and migrants languages.